New product practices and performance of German appliances companies - Dąbrowski, Dariusz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
An efficient new product strategy for German industry of household appliances, requires being first in the market. Concept testing, concept screening, marketing plan development and market introduction are new product process activities which have a positive impact on new product performance in the industry. Also applying project matrix and outsourcing prototyping or tooling are an effective means of new product development for German producers of household appliances
Argumenta Oeconomica, 2008, No 2 (21), s. 153-176
Keywords: new product development; product performance